ZMIANY SKŁADU OSOBOWEGO SPÓŁKI CYWILNEJ - Stanik, Mariusz (Zeszyty Prawnicze, 2017)
Changes in Member’s Structure of Civil Law Partnerships Summary The text concerns analysis of causes of changes in membership of civil law partnerships. In the first place the author briefly analysed the nature of civil law partnerships. Secondly, there is a legal analysis of causes of change in membership: withdrawal from the partnership by member’s notice, withdrawal from the partnership without member’s notice due to justified reasons, withdrawal from the partnership by member’s personal creditor notice, withdrawal from the partnership by member’s death or by recognition of member’s death, accession of the dead member’s heirs, accession of the new member, exclusion of the member and transfer of the membership. Analysis of the issue includes regulation of the Polish Civil Code, opinions expressed in the civil jurisprudence and court judgments.